MODIFIKASI MODEL INDEKS JANSEN SEBAGAI ALAT UKUR KINERJA SAHAM SYARIAH - Mohammad Farhan Qudratullah (I-Finance Journal, 2019)
The Jansen Index is a measure of stock performance based on the Capital Asset Princing Model (CAPM). The Jansen Index consists of 4 (four) components, namely: stock returns, beta stocks, market returns, and risk-free returns. Many studies approach risk-free returns with interest rates when measuring the performance of Islamic stocks in the Jansen Index model, while interest rates are prohibited in the concept of Islamic finance. This paper discusses the modification of the Jansen Index model to analyze the performance of Islamic stocks with 4 (four) approaches, namely the model without interest rates, models with zakat rates, models with inflation, and models with gross domestic production (GDP) and compare them with models with interest rates (BI-Rate). Then the five models are implemented in the Islamic capital market in Indonesia in the period January 2011 - July 2018.The results obtained are that there is a very high suitability for the measurement results of the five models. Judging from the closeness of the results of performance measurement, the five models can be grouped into 2 (two), namely models with interest rates, inflation, and GDP as the first group, while models without interest rates and zakat- rate as the second group. This means, on the concept of Islamic finance, risk-free returns can be measured using these 4 (four) approaches, specifically inflation or GDP